Heidegger und der Nationalsozialismus: drei Biographien und eine Monographie - Poppenberg, Gerhard (Philosophische Rundschau, 2023)
Following the publication of the Schwarze Hefte, the question of Heidegger's relation with German National Socialism arose again with renewed intensity. The books reviewed are three biographies and a monograph treating the life and work of Heidegger with a focus on his commitment to National Socialism. The biographies make use not only of the volumes of the Schwarze Hefte, but also of the widely spread new sources, e.g. of Heidegger's letters published during the last two decades, and provide - with various degrees of philosophical insight - new interpretations of Heidegger's commitment. The monograph tries to give an interpretation of the entire work centred around and resting upon Heidegger's political attitude.Thomas Rohkrämer, Martin Heidegger. Eine politische Biographie. Paderborn: Schöningh, 2020, 297 S. - Lorenz Jäger, Heidegger. Ein deutsches Leben, Berlin: Rowohlt 2021. 606 S. Guillaume Payen, Heidegger. Die Biographie, Darmstadt: WBG / Theiss, 2022. 703 S.; französisches Original: Martin Heidegger. Catholicisme, Révolution, Nazisme, Paris: Perrin, 2016. - Oliver Precht, Heidegger. Zur Selbst- und Fremdbestimmung seiner Philosophie, Hamburg: Meiner, 2020. 312 S.